Improving Climate Literacy of High School Students through Physics Teaching Materials based on STEM - Hakim, A.; Efwinda, S.; Damayanti, P.; Syam, M.; Mutmainah, O.; Norsaputra, A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Climate change is a problem that has received attention from various countries around the world. Climate change disrupts the balance of the ecosystem, which, if allowed to continue, can threaten the continuity of life on Earth. In education, addressing the challenges of learning about climate change can be done by selecting appropriate teaching materials. This study aims to examine Science, Technology, Engineering, and Mathematics (STEM) based physics teaching materials on climate change developed and designed to improve the climate literacy of high school students. The research uses the Analyze, Design, Development, Implementation, and Evaluation (ADDIE) Model. The teaching materials developed are then implemented in learning climate change in high school students. The research design was one group pretest-posttest with a sample of 37 high school students in Indonesia. The sampling technique used cluster random sampling. The instrument used was a test technique for the aspects of knowledge and action consisting of 30 multiple-choice questions and a questionnaire for the attitude aspect comprising 15 statements. The results show that the STEM-based physics teaching material on climate change improves the climate literacy of Indonesian high school students, with an average N-Gain score of 0.51 in the moderate category. Based on these results, it can be concluded that STEM-based teaching materials on climate change materials can be used to improve the climate literacy of high school students.